Influence of dietary supplementation of modified tall oil and vitamin e on bacon characteristics - Waylan, A.T.; O'Quinn, P.R.; Woodworth, J.C.; Koo, S.I.; Unruh, John A.; Goodband, Robert D.; Nelssen, Jim L.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Seventy-two crossbred (PIC) barrows were used to determine the influence of feeding modified tall oil (MTO, 0 or .5% of diet) and vitamin E (0, 10, or 50 IU/lb of feed) on bacon quality characteristics. Feeding MTO to pigs during both. the growing and finishing phases increased bacon slice firmness. Feeding swine MTO and vitamin E had minimal effects on bacon production, proximate analysis, and quality traits. Therefore, any of these combinations of MTO with vitamin E can be fed to swine to improve carcass traits without affecting bacon.
Keywords: Swine; Modified tall oil; Vitamin E; Bacon